Coupling Relationship Between Transportation Corridors and Ecosystem Service Value Realization in Giant Panda National Park - Lulin Liu; Renna Du; Qian Mao; Gaoru Zhu; Hong Zhong (Land)
As critical zones for ecological conservation, national parks necessitate integrated management of transportation corridors (TCs) and ecosystem service value (ESV) to advance ecological civilisation. This study investigates the TC-ESV mutual construction mechanism in the Giant Panda National Park (GPNP). This research employs the TOPSIS method to measure the development level of TCs, applies the equivalent factor method to calculate the ESV, and uses a coupling coordination model and local spatial autocorrelation analysis to evaluate their interaction patterns. The results show that TC development in the GPNP has been increasing, accompanied by a significant rise in ESV. A coupling coordination relationship exists between TCs and ESV, with notable spatial differentiation. TCs not only increase the market ESV by reducing distribution costs and facilitating the outward flow of ESV, they also improve the accessibility of national parks, promote ecotourism and cultural services, facilitate the movement of people and the exchange of knowledge, and enhance the ability of local populations and migrants to realise the ESV in the long term. However, challenges persist, including ESV conversion difficulties and TC construction’s potential impacts on ESV realisation. Therefore, we propose optimised green transport corridors and differentiated ecological compensation mechanisms, and by analysing the interaction between them, the innovation of this paper is to provide an innovative framework for sustainable spatial governance of ESV conversion and TC development in national parks, enriching the interdisciplinary approach.